KONSEP ASBÂB AL-NUZUL DALAM ‘ULUM AL-QURAN - Munjin, Shidqy (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2019)
Abstract : The Quran is not a book that goes down in a vacuum culture. The Qur'an always comes down to answer all the problems. So every verse that descends, must be understood as the context or challenges it faces. In 'ulûm al-qurân this problem is called asbâb al-nuzûl.This paper attempts to explain various scholars' views on the science of asbâb al-nuzûl and some information about the technical application of ayat. This paper provides enough evidence that the ‘ilm of asbâb al-nuzûl that has been compiled by the scholars from generation to generation can be called established and comprehensive.Key Word : al-Quran, ‘ulûm al-Qurân, asbâb al-nuzûl. Abstrak : Al-Quran bukanlah kitab yang turun dalam keadaan vakum budaya. Al-Quran selalu turun untuk menjawab semua problem yang ada. Maka setiap ayat yang turun, harus difahami sebagaimana konteks atau tantangan yang sedang dihadapinya. Dalam ‘ulûm al-qurân permasalahan ini disebut dengan asbâb al-nuzûl.Tulisan ini mencoba menerangkan berbagai pandangan ulama mengenai ilmu asbâb al-nuzûl serta beberapa keterangan mengenai teknis penerapannya terhadap ayat. Tulisan ini cukup memberikan bukti bahwa ilmu asbâb al-nuzûl yang telah disusun oleh para ulama dari generasi ke generasi sudah bisa disebut mapan dan komprehensif.Kata Kunci : al-Quran, ‘ulûm al-Qurân, asbâb al-nuzûl.